Biosensors for detection of paralytic shellfish toxins: Recognition elements and transduction technologies. (March 2023) - Wei, Liu-Na; Luo, Lin; Wang, Bing-Zhi; Lei, Hong-Tao; Guan, Tian; Shen, Yu-Dong; Wang, Hong; Xu, Zhen-Lin
Abstract: Background: Paralytic shellfish toxins (PSTs) are biotoxins derived from harmful algal blooms and cause paralytic shellfish poisoning (PSP). PSTs are widely found in natural waters, indicating that they can cause human death through food chain and economic losses of aquatic species worldwide. Therefore, accurate, sensitive, and efficient methods are needed for the detection of PSTs in the environment and food. Scope and approach: Biosensor is one of the fastest-growing detection methods since they are simple, sensitive, portable, and efficient for real-time or near real-time analyses. This article provides a comprehensive review of PSTs biosensors by highlighting different signaling mechanisms (electrochemical, optical, etc.). Typically, the effects of the generation of bio-recognition elements on PSTs sensing performance to expand new biosensors applications which were highlighted. Key findings and conclusions: Although mouse bioassay and HPLC are the current methods used for PSTs detection, biosensor could become an alternative method for PSTs detection in the future. Although antibodies are the most popular affinity-based recognition elements, aptamers have been rapidly developed in recent years to mimic antibodies. As a result, biosensor detection of PSTs mainly focuses on electrochemical and optical signal transduction. Nonetheless, robust, accurate, and portable biosensors are needed for real application and commercialization. Graphical abstract: Image 1 Highlights: MerIts and demerits of bio-recognition elements for detceting PSTs were summarized. Recent advanced biosensors methods for paralytic shellfish toxins was reviewed. Electrochemical and optical signal transduction based biosensors had been strengthen. AntiBodies and adaptors showed potential for development of practical biosensors.